Supply Chain Risk Management in der Industrie - am Beispiel der Metall- und Elektroindustrie - Frank Bayer; Sascha Bioly (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2014)
– Today industrial enterprises are confronted with an increasing trend to focus on their core capabilities. By outsourcing certain activities to logistics providers or suppliers a company has the possibility to create a lean organization and decrease fixed costs. As a result supply chains gain complexity and the dependency on third parties rises which bears new risks for the functionality of the value network. While in the past only risks connected to internal processes were analyzed a contemporary approach is pursuing the theory that risks can move along supply chains and influence the operations of multiple supply chain partners. Because of that Supply Chain Risk Management was introduced as a new academic discipline that deals with the identification, evaluation and mitigation of such risk factors. The present working paper explains the theoretical background of Supply Chain Risk Management and transfers the findings to a company belonging.
Keywords: 650